Microscopic Examination of Urine Samples as the Early Detection of Asymptomatic Urinary Tract Infection in Pregnant Women: A Cross-Sectional Study: Uji Mikroskopik Spesimen Urin sebagai Deteksi Dini Infeksi Saluran Kemih tidak Bergejala pada Perempuan Hamil: Sebuah Studi Potong Lintang - Yeva Rosana; Dwiana Ocviyanti; Rahmah Amran (Indonesian Journal of Obstetrics and Gynecology, 2019)
Abstract Objectives:To investigate the role of microscopic examination of urine sample in supporting early diagnosis of asymptomatic urinary tract infection (UTI) in pregnant women. To compare correspondence between microscopic examination and urine culture result as a gold standard diagnostic modality to support the diagnosis of UTIs and as an evidence-based to start empirical therapy. Methods: Microscopic analysis was conducted in 74 centrifuged and non-centrifuged urine samples from 317 pregnant who came to six healthcare centres in Jakarta, which showed a positive result of nitrite examination. The results of the microscopic examination of bacteriuria and leukocyturia were compared with a urine culture. Results: Sensitivity of centrifuged bacteriuria was the highest among the other microscopic parameters, which was 74% with the p-value of 0.009. Combination of bacteriuria and leukocyturia≥3/HPF dan≥5/HPF have increased the specificity with the value of 91.5% and 93.6% in non-centrifuged urine. Conclusion: This result showed that the best method of microscopic examination for early diagnosis of asymptomatic urinary tract infection in pregnant women is the detection of bacteriuria in centrifuged urine. Combination of bacteriuriaandleukocyturiatest, as well as leukocyturia≥3/HPF and≥5/HPF, can be used to rule out the diagnosis of UTI at an early stage. Keywords: asymptomatic urinary tract infection, bacteriuria, leukocyturia,microscopic examination, urine culture. Abstrak Tujuan: Mengetahui peran pemeriksaan mikroskopis sampel urin dalam mendukung diagnosis dini infeksi saluran kemih asimptomatik (ISK) pada perempuan hamil. Membandingkan kesesuaian antara pemeriksaan mikroskopis dan hasil kultur urin sebagai modalitas diagnostik standar emas untuk mendukung diagnosis ISK dan sebagai dasar bukti untuk memulai terapi empiris. Metode: Penelitian uji mikroskopik dilakukan pada 74 sampel urin disentrifugasi dan tidak sentrifugasi, dari 317 sampel urin perempuan hamil yang berobat ke-enam puskesmas di Jakarta dengan uji nitritpositif. Hasil uji mikroskopik bakteri uria dan leukosit uria dibandingkan dengan hasil kultururin. Hasil: Sensitivitas bakteriuria yang disentrifugasi menunjukan hasil yang paling baik dibandingkan dengan parameter uji mikroskopik lain, yaitu 74% dengan nilai p yang bermakna sebesar 0,009. Kombinasi bakteri uria dan leukosituria ≥3/LPB dan ≥5/LPB dapat meningkatkan spesifisitas uji dengan nilai 91,5% dan 93,6% pada urin yang tidak disentrifugasi. Kesimpulan: Hasil menunjukkan bahwa bakteri uria pada urin yang disentrifugasi, merupakan metode yang paling baik untuk membantu diagnosis dini ISK tidak bergejala pada perempuan hamil. Uji kombinasi bakteri uria dan leukosituria, serta uji leukosituria ≥3/LPB dan ≥5/LPB dapat dimanfaatkan untuk membantu secara dini menyingkirkan orang yang tidak mengalami ISK. Kata kunci: bakteriuria, infeksi saluran kemih tidak bergejala, kultur urin,leukosituria, uji mikroskopik